2017
DOI: 10.1177/1073191117706139
|View full text |Cite
|
Sign up to set email alerts
|

Validity in Phallometric Testing for Sexual Interests in Children: A Meta-Analytic Review

Abstract: Valid assessment of pedohebephilic interests (i.e., sexual interest in children) is fundamental to forensic clinical practice. Phallometric testing-which measures changes in penile circumference or volume, while stimuli depicting different ages and sexual activities are presented-is widely used in clinical and research settings to detect such interests. This meta-analysis summarizes studies comparing sexual offenders against children and various types of controls on phallometric tests for pedohebephilic intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 76 publications
1
45
0
Order By: Relevance
“…A current large meta-analysis (N = 6,785 subjects) suggests that several phallometric testing procedures are valid indicators of pedohebephilic interest (i.e., prepubescent and pubescent children) with small to large effect sizes. Moreover, phallometric tests were able to predict sexual reoffending with moderate effect sizes (N = 2,709 subjects) (108). A recent large study (N = 1,136) showed that most sex offenders against children (83%) were unable to successfully suppress their sexual arousal to pictures depicting children when instructed to do so.…”
Section: Penile Plethysmographymentioning
confidence: 94%
“…A current large meta-analysis (N = 6,785 subjects) suggests that several phallometric testing procedures are valid indicators of pedohebephilic interest (i.e., prepubescent and pubescent children) with small to large effect sizes. Moreover, phallometric tests were able to predict sexual reoffending with moderate effect sizes (N = 2,709 subjects) (108). A recent large study (N = 1,136) showed that most sex offenders against children (83%) were unable to successfully suppress their sexual arousal to pictures depicting children when instructed to do so.…”
Section: Penile Plethysmographymentioning
confidence: 94%
“…Because sexual arousal to children is another strong predictor of engaging in sexual behavior with children in adjudicated sexual offenders [48,49], providing cognitive and behavioral techniques for managing sexual arousal may improve non-offending pedophiles' ability to manage sexual urges in their daily lives. This treatment focus is supported by recent research that finds self-reported pedohebephilic sexual interests are associated with markers of sexual preoccupation, such as higher rates of masturbation and higher frequency of sexual fantasies [23,24].…”
Section: Treatment With Non-offending Pedophilesmentioning
confidence: 98%
“…For the first and second criteria, the PPG has been the subject of numerous studies that have been published in peer‐reviewed journals. Although there is a long history of research on the PPG, within the last 5 years specifically, it has been studied using samples of men with pedophilic interests (Müller et al, ), examining attempts to dissimulate (Babchishin, Curry, Fedoroff, Bradford, & Seto, ; Trottier, Rouleau, Renaud, & Goyette, ), comparisons of PPG laboratories, techniques, and standardization (Demidova et al, ; Murphy & Fedoroff, ; Murphy, Ranger, Stewart, et al, , Murphy, Ranger, Fedoroff, et al, ), PPG stimuli (Dennis, Rouleau, Renaud, Nolet, & Saumur, ; Murphy et al, ; Murphy, Ranger, Fedoroff, Burke, & Dwyer, ; Rosetti et al, ), and meta‐analytic techniques (McPhail et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the error rate of the PPG, previous research has demonstrated that the PPG can accurately discriminate between men convicted of sex offenses against children from those who have not (e.g., Barbaree & Marshall, 1989;Freund & Blanchard, 1989;Lalumiere & Quinsey, 1994;McPhail et al, 2019). No test is without its limitations; however, widely accepted medical tests (e.g., hematologic blood values, endocrinologic hormone levels, blood pressure measurements, HIV screening tests) develop cut scores that balance specificity and sensitivity (e.g., Tan et al, 2016;Waaler, 1980).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation